2011
DOI: 10.1136/bmj.d5094
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A supplements for preventing mortality, illness, and blindness in children aged under 5: systematic review and meta-analysis

Abstract: Objective To determine if vitamin A supplementation is associated with reductions in mortality and morbidity in children aged 6 months to 5 years.Design Systematic review and meta-analysis. Two reviewers independently assessed studies for inclusion. Data were double extracted; discrepancies were resolved by discussion. Meta-analyses were performed for mortality, illness, vision, and side effects.Data sources Cochrane Central Register of Controlled Trials (CENTRAL) in the Cochrane Library, Medline, Embase, Glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
193
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(206 citation statements)
references
References 86 publications
5
193
1
7
Order By: Relevance
“…VAD is still a major public health problem worldwide, which has contributed substantially to the health threat among young children and women of reproductive age in developing coutries. VAD in pregnant women is associated with night blindness, severe anaemia, wasting, malnutrition, and reproductive and infectious morbidity, and increased risk of mortality 1-2 years following delivery [31]. Several previous studies have demonstrated that VAD induces congenital heart, ocular tissues, respiratory, urogenital and circulatory systems, and skeletal deformities in experimental animals including monkeys, rabbits, rats, mice and hamsters [22].…”
Section: Discussionmentioning
confidence: 99%
“…VAD is still a major public health problem worldwide, which has contributed substantially to the health threat among young children and women of reproductive age in developing coutries. VAD in pregnant women is associated with night blindness, severe anaemia, wasting, malnutrition, and reproductive and infectious morbidity, and increased risk of mortality 1-2 years following delivery [31]. Several previous studies have demonstrated that VAD induces congenital heart, ocular tissues, respiratory, urogenital and circulatory systems, and skeletal deformities in experimental animals including monkeys, rabbits, rats, mice and hamsters [22].…”
Section: Discussionmentioning
confidence: 99%
“…Given that the study population is deficient in vitamin A 13 and has a high burden of infections, 21 this apparent lack of benefit was unexpected, especially as vitamin A supplementation in children between the ages of 6 months and 5 years in similar populations has reduced allcause mortality and mortality from diarrhoeal diseases. 2 The trial had adequate power to examine the effect of vitamin A supplementation on pregnanc yrelated deaths. It also had adequate power to examine the effect of such supplementation on rates of infection, as these were more common, among CI, confidence interval; RR, rate ratio.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although in these countries allcause mortality among young children (i.e. children aged from 6 months to 5 years) can be reduced by administering vitamin A supplements, 2 there is little evidence that such supplements are beneficial among adults. In a meta-analysis of trials in which adults were given antioxidant supplementation, supplements of vitamin A (alone or combined with other antioxidants) were found to have either no effect on all-cause mortality or to increase such mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The Panel is aware of other studies which looked at possible associations between preformed vitamin A intake or blood retinol concentration and adverse health outcomes (Grotto et al, 2003;Bjelakovic et al, 2008;Chen et al, 2008;Mayo-Wilson et al, 2011;Beydoun et al, 2012;Bjelakovic et al, 2012;Bjelakovic et al, 2013;Field et al, 2013;Bjelakovic et al, 2014). Available data on individual outcomes are limited or relate to interventions that used large doses of retinol (≥ 6 000 µg) once or several times a year, which are difficult to relate to a potential effect of daily dietary intake of retinol.…”
Section: Excessmentioning
confidence: 99%